Corticosteroid modulation of immunoglobulin expression and B‐cell function in COPD. Issue 5 (17th February 2016) - Lee, Jin; Machin, Matthew; Russell, Kirsty E.; Pavlidis, Stelios; Zhu, Jie; Barnes, Peter J.; Chung, Kian F.; Adcock, Ian M.; Durham, Andrew L.
Abstract : We investigated changes in gene expression that occur in chronic obstructive pulmonary disease (COPD) after corticosteroid treatment and sought to identify the mechanisms that regulate these changes. Biopsy samples were taken from patients with COPD (Global Initiative for Chronic Obstructive Lung Disease stage I to II) before and after treatment with fluticasone propionate (FP)/salmeterol (SM) (50/500, 4 wk). Gene expression was measured by microarray and was confirmed by real‐time reverse transcription‐quantitative PCR (RT‐qPCR). The effect of FP on IgG expression and B‐cell proliferation in the presence of oxidative stress was also studied. FP/SM significantly increased the expression of 180 genes while repressing 343 genes. The top 5 downregulated genes were associated with immunoglobulin production, whereas the immunomodulatory FK506 binding protein ( FK506BP ) was up‐regulated. Genes including IL6, IL8, and TBET‐encoding TBX21 were unaffected. FP reduced IgG protein and mRNA expression and proliferation of human B cells through the dephosphorylation of ERK‐1/2 via increased DUSP1 (dual‐specificity protein phosphatase 1) expression. Consistent with in vivo data, oxidative stress did not prevent FP‐induced suppression of IgG expression in human B cells in vitro. Changes in expression were validated by RT‐qPCR and by gene set enrichment analysis in distinct COPD cohorts. FP may reduce the adaptive immune response in COPD and may be more effective in patients with an increased B‐cell/antibody response indicated by high autoantibody titers.—Lee, J., Machin, M., Russell, K. E., Pavlidis, S., Zhu, J., Barnes, P. J., Chung, K. F., Adcock, I. M., Durham, A. L. Corticosteroid modulation of immunoglobulin expression and B‐cell function in COPD. FASEB J. 30, 2014–2026 (2016). www.fasebj.org